2020
DOI: 10.1055/a-1220-6389
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic limitations of magnifying endoscopy with narrow-band imaging in early gastric cancer

Abstract: Background and study aims Magnifying endoscopy with narrow band imaging (M-NBI) has made a huge contribution to endoscopic diagnosis of early gastric cancer (EGC). However, we sometimes encountered false-negative cases with M-NBI diagnosis (i. e., M-NBI diagnostic limitation lesion: M-NBI-DLL). However, clinicopathological features of M-NBI-DLLs have not been well elucidated. We aimed to clarify the clinicopathological features and histological reasons of M-NBI-DLLs. Patients and methods In this sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These findings are also thought to stem from the growth pattern of GA-FG, as mentioned above. On magnifying endoscopy according to MESDA-G, GA-FG was diagnosed as non-cancerous in all cases and is considered to be one of the lesions subject to M-NBI diagnostic limitations [ 26 ]. With respect to GA-FGM, however, the prevalence of the four features on M-NBI, except for dilatation of IP, was low at about 30%.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also thought to stem from the growth pattern of GA-FG, as mentioned above. On magnifying endoscopy according to MESDA-G, GA-FG was diagnosed as non-cancerous in all cases and is considered to be one of the lesions subject to M-NBI diagnostic limitations [ 26 ]. With respect to GA-FGM, however, the prevalence of the four features on M-NBI, except for dilatation of IP, was low at about 30%.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients are diagnosed with advanced tumors as soon as they are checked, and have lost the opportunity for surgery. Obviously, this diagnostic method has certain limitations [21]. Early diagnosis of cancer is the key to improving the overall survival rate of patients, reducing disease-free progression, and reducing the risk of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, this can be corrected by DL about cases that are difficult to diagnose and diagnostic limitations of EGCs, which will surely reduce false negatives and improve the negative predictive value significantly. Furthermore, we excluded ME‐NBI images of GAFG and diffuse‐type EGC to keep the quality of the AI‐assisted CNN‐CAD system, because some previous studies have reported that they should be dealt as the diagnostic limitations of ME‐NBI by VSCS 3,33 . However, we should evaluate the diagnostic ability of the AI‐assisted CNN‐CAD system for diagnostic limitation cases such as GAFG and diffuse‐type EGC for application to real clinical settings in future.…”
Section: Discussionmentioning
confidence: 99%